Mosque library and its role in intellectual life of the nation - Rahmawati, Triani (2012)
This paper discuss the mosque library and its role in the intellectual life of the nation. The mosque as a place of worship for Muslims can facilitate the community in getting information through the library. The mosque library in Indonesia is very important, because the Indonesian people are Muslim majority and they have low read interest. The existence of the mosque library did not escape the attention of the National Library of Indonesia as a patrons of libraries in Indonesia. The National Library of Indonesia proclaimed empowerment movement of library to develop read interest society as a manifestation of community education. Empowerment movement of the library is done by building different types of libraries, such as mobile library, school libraries (including boarding school libraries), and a place of worship libraries, one of which is the mosque library. In this paper the mosque libraries that is studied is Masjid Raya Pondok Indah, which is located in South Jakarta and Masjid Istiqlal, in Central Jakarta. The scope of study includes the collections, services, users, librarians, library space, and the development of the library. From observations we can conclude that the mosque libraries have a role in improving the reading interest of Indonesian society, so that the ideals of the nation of Indonesia in the intellectual life of the nation by improving the quality of human resources can be realized.